Reconstructing Character Education Through Semiotic Analysis of Wall-E in Islamic Education: Media Literacy, Humanitarian Ethics, and Socio-Political - Ifham Choli; Nanda Khairiyah; Siti Zulfa Alawiyah; Zakiah Rijanati (GHAITSA : Islamic Education Journal, 2026)
The increasing dominance of technology and consumer culture has intensified various humanitarian crises, including environmental degradation, declining social empathy, and the erosion of moral agency. These challenges pose significant concerns for character education, particularly within Islamic education, which emphasizes humanitarian ethics, social responsibility, and ethical citizenship. This study aims to reconstruct character education through a semiotic analysis of the animated film WALL-E and to examine its relevance as a pedagogical medium for media literacy in the context of Islamic education. Using a qualitative research design, this study applies Roland Barthes’ semiotic framework denotation, connotation, and myth to analyze selected visual and narrative scenes from WALL-E. The analysis focuses on how humanitarian crises are visually represented and how these representations generate educational meanings relevant to character formation. Data were collected through repeated observation of the film and supported by scholarly literature on semiotics, character education, media literacy, and Islamic education. The findings indicate that WALL-E constructs a coherent set of reconstructed educational values, including ecological responsibility, moral agency toward technology, social empathy, critical thinking, collective responsibility, and socio-political awareness. At the mythological level, the film critiques technological domination and consumerism while offering a vision of moral reconstruction grounded in human dignity and ethical engagement with society and nature. By synthesizing semiotic interpretation and educational theory, this study proposes a semiotic-based framework for character education that positions animated film as a reflective learning resource in Islamic education. This research contributes to educational discourse by bridging visual representation, humanitarian ethics, and socio-political awareness in character education for the digital age.